Application of dolomite as a heterogeneous catalyst of biodiesel synthesis - Sendžikienė, Eglė; Makarevičienė, Violeta; Kazancev, Kiril (Transport, 2018)
Some of the more recent methods of obtaining biodiesel are based on heterogeneous catalysis, which has the advantage of multiple uses of a catalyst. Natural minerals, such as dolomite, opoca and serpentinites, could be promising for use in biodiesel synthesis. The purpose of this study was to optimise the reaction conditions for biodiesel synthesis from sunflower oil and methanol using dolomite as a catalyst. Optimum reaction conditions for the transesterification of sunflower oil with methanol, using dolomite calcined at the temperature of 850 °C, have been identified: the amount of the catalyst – 6%, the molar ratio of methanol to oil – 8:1, the reaction duration – 5 hours and the reaction temperature – 60 °C. The amount of Fatty Acid Methyl Esters (FAME) of the sunflower oil obtained – 97.6%. FAME is in conformity with the EN 14214:2003 standard, when 500 ppm of antioxidant Ionol and 500 ppm of depressant Infineum R-442 are added. The Cold Filter Plugging Point (CFPP) of FAME is reduced to7 °C by adding 500 ppm of Infineum R-442. This product can be used in summer in the countries that are placed in Class E, including Lithuania. It has been established that dolomite without regeneration can be used for the transesterification of sunflower oil 2 times.